The Role of Public Governance Practices for Business R&D Activity in the EU - Dejan Ravšelj; Sabina Hodžić (Central European Public Administration Review)
The public sector and public governance play a crucial role in the contemporary society which takes care of social needs. Therefore, it is not surprising that good governance has often been used to explain good economic performance as well as the well-being of a society over the last decade. However, the business sector often represents a channel through which public governance affects economic performance, which has largely been neglected in the existing literature. In this context, not much is known about the role of public governance in promoting research and development (R&D) in the business sector in the EU. Therefore, this article aims to explain the interaction between the public and business sectors in a cross-national setting by investigating the relationship between different public governance practices and business R&D activity. The aim is to be achieved by applying a multiple regression analysis on a cross-sectional dataset of EU member countries. The empirical results show the following. First, they reveal that, in general, public administration in the EU is predominantly based on neo-Weberian state rather than New Public Management governance practices. Second, they reveal that public governance practices have important implications for business R&D activity. They show that impartiality, accountability and efficiency enhance business R&D activity in the EU, while closeness deteriorates it. The findings of the article are especially beneficial for contemporary governments and policymakers to establish appropriate public governance and policy practices in the future.